Sustainable Development Goals (SDGs), Socio Energy and Socio Sustainability - Paisal Halim; Syamsiah Badruddin; Muhammad Ikhsan Setiawan; Agus Sukoco; Muhammad Isradi; Sugeng Sugeng; Muhammad Ashlyzan Razik (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Year 2020 until 2021, there are increase of documents based on Sustainable Development Goals (SDGs), Socio Energy documents published in SCOPUS.COM. Subject area Documents, first Environmental Science, followed Energy, and Social Sciences. Documents by funding sponsor, Compare the document counts for up to 15 funding sponsors, dominant European Commission, Documents by affiliation, Compare the document counts for up to 15 affiliations, dominant University of KwaZulu-Natal. Design/methodology/approach: Documents per year by source, dominant Sustainability Switzerland journal, Documents by country or territory, Compare the document counts for up to 15 countries/territories, first United Kingdom, followed Nigeria and United States. In ASIA first China, followed Japan and India. In ASEAN first Malaysia and Thailand, there are no Indonesia, weakness. There are increase of documents based on Sustainable Development Goals (SDGs), Socio Sustainability documents published in SCOPUS.COM. Findings: Documents by funding sponsor, Compare the document counts for up to 15 funding sponsor. First Chinese Academy of Sciences, followed National Natural Science Foundation of China, Centre for International Forestry Research, Deutsche Forschungsgemeinschaft, Directorate-General for the Environment, and Engineering and Physical. Documents per year by source, first Sustainability Switzerland journal, followed International Journal Of Sustainable Development And World Ecology, and International Organisations Research Journal. Compare the document counts for up to 10 sources. Documents by affiliation, Compare the document counts for up to 15 affiliations, first Chinese Academy of Sciences. University of Leeds, followed University of Southampton, European Commission Joint Research Centre, Universitas Indonesia, Institut Teknologi Bandung, and Universitas Sumatera Utara. Documents by country or territory, Compare the document counts for up to 15 countries/territories, first United Kingdom, second South Africa, third Italy. First in ASIA China, First in ASEAN Indonesia. Subject area Documents, first Social Sciences, and Environmental Science. Paper type: Research paper